Implementasi Kebijakan Pengembangan Pariwisata Pasca Pandemic di Indonesia - Ihin Solihin; Jumanah Jumanah; Arif Nugroho; Yuni Dwi Cahyani; Ikhda Ratri Auladatisyifa; Riyan Herdiana (Jurnal Administrasi dan Kebijakan Publik, 2023)
The Covid-19 outbreak emerged in early 2020, crippling global economic activities, including the tourism sector in Indonesia. The decline in the number of tourists visiting Indonesia had a significant impact on the country's economy. It is a significant responsibility for the government to formulate policies for the post-pandemic development of tourism in Indonesia. One of the policies for the development of the tourism sector is the concept of the "new normal." This policy must be effectively implemented to revive tourism in Indonesia. The method used in writing this article employs a literature review study method. This method involves reviewing research from Google Scholar's database and relevant articles related to the discussed topic, which are then processed using appropriate tools. Based on the results of the literature review study, the implementation of post-pandemic tourism development policies in Indonesia involves three elements: sustenance, self-esteem, and freedom from servitude. These elements are realized when the health protocol requirements in the new normal setting are adhered to. These three elements are significant considerations for the government when deciding whether to reopen or postpone operations in the tourism sector due to their profound social, economic, and environmental impacts. Other government strategies or efforts in implementing tourism development policies in the era of the new normal include promoting local tourism, emphasizing voluntarism and solidarity, and making policies based on sustainable development